2012
DOI: 10.1021/bc200433s
|View full text |Cite
|
Sign up to set email alerts
|

SiRNA Delivery Systems Based on Neutral Cross-Linked Dendrimers

Abstract: A neutral cross-linked dendritic system is described for use of delivering small interfering RNA (siRNA) for targeted gene silencing. By replacing the terminal amines with hydrazide groups and N-acetylgalactosamine (GalNAc) ligands, cationic polyamidoamine (PAMAM) dendrimers were transformed into neutral glycosylated carriers for siRNA delivery. Mainly owing to the pH sensitivity and the proton-absorption capability of the tertiary amines within the interior branches, these PAMAM derivatives showing neutrality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…6). 66,68,69,73 For preparing PAMAM glycodendrimers as a drug delivery system [85][86][87][88][89][90][91][92][93][94] various carbohydrate units with acid, lactone or phenyl isothiocyanate groups were converted Characteristics of open shell and dense shell PPI glycodendrimers. Open shell is characterized by peripheral amino group wearing maximal one (oligo-)saccharide unit in PPI-OS-Mal G3, while peripheral amino groups in dense shell of PPI-DS-Mal G3 possess two chemically coupled (oligo-)saccharide units.…”
Section: Synthetic Aspects Of Dendritic Glycopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…6). 66,68,69,73 For preparing PAMAM glycodendrimers as a drug delivery system [85][86][87][88][89][90][91][92][93][94] various carbohydrate units with acid, lactone or phenyl isothiocyanate groups were converted Characteristics of open shell and dense shell PPI glycodendrimers. Open shell is characterized by peripheral amino group wearing maximal one (oligo-)saccharide unit in PPI-OS-Mal G3, while peripheral amino groups in dense shell of PPI-DS-Mal G3 possess two chemically coupled (oligo-)saccharide units.…”
Section: Synthetic Aspects Of Dendritic Glycopolymersmentioning
confidence: 99%
“…1,33,35 On the other hand dendritic glycoconjugates, carbohydrate-containing dendronized polymers, and hybrid materials of various polysaccharides over the last year have been also established in various application fields. Thus they have been used as drug delivery systems, 10, biosensors, 15,16,19,[96][97][98][99][100][101] and imaging agents, 1,18,[102][103][104][105][106] but also as a base in biohybrid structures obtained through non-covalent and biological conjugation, 91,92,107,108 as sugarballs for H-bond-active therapeutics and diagnostics for brain disease, [109][110][111][112][113][114][115][116][117][118] as supramolecular structures by (defined) self-assembly [119][120][121] or host-guest interactions, 122 and in thin film technology for introducing specific interactions with small analyte molecules or proteins. 123,124 The PPI, Lys, and PAMAM polyamine dendrimers, but also branched poly(ethyleneimines) (PEI) are the dominating dendritic core scaffolds to realize the desired dendritic glycopolymers for these growing research fields ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…48 In short, this thioacetal was prepared in one step from 4,5-dimethoxy-6-nitrobenzaldehyde (6nitroveratraldehyde) by reacting with 2-mercaptoethanol (2 × 2.5 mol equiv) in dichloromethane containing a mixture of acetic acid and BF 3 1.32 (m, 3H, Dox-6') ppm. 13 Figure 3). Details for 10 preparation 36 and its conjugation with 3 and G5(FA) 6 are described in Supporting Information.…”
Section: Tnb(oh)mentioning
confidence: 99%
“…Indeed, Gal, lactose and GalNAc have been exploited as ligands in delivery systems in the treatment of hepatic diseases [45]. Through hydrazone linkages, our laboratory created a small library of glycosylated dendrimers using G5 PAMAM and studied how these conjugates interact with HepG2 cells [45,46]. The results showed that Gal-, lactose-and N-acetylglucosamine (GlcNAc)-modified PAMAM had significantly higher avidity towards HepG2 cells compared with other saccharide-modified dendrimers in the library.…”
Section: Cell-binding Properties Of Bioactive Dendrimer Conjugates Inmentioning
confidence: 99%
“…By replacing the terminal amines with hydrazide groups and GalNAc ligands according a method described above [45], cationic PAMAM dendrimers were transformed into neutral glycosylated carriers. Anti-luciferase siRNA was complexed to these protonatable dendrimers at pH 5 via electrostatic interaction [46]. The hydrazides on the PAMAM periphery were then cross-linked with homobifunctional glutaraldehyde to retain encapsulated siRNA following pH neutralization.…”
Section: Delivery Via Saccharide-conjugated Dendrimersmentioning
confidence: 99%